In Vitro Study of the Effects of Pesticide Mixtures Used in Maize Cultivation in Ecuador - Ana Paulina Arévalo-Jaramillo; Jackeline Elizabeth Guamán Hurtado; Gabriela Cevallos-Solorzano; Natalia Bailon-Moscoso (Toxics)
Ecuador, located in South America, ranks among the countries with the highest rates of pesticide use per unit of cropland. Pesticide exposure is linked to genotoxic effects and carcinogenicity. While most studies evaluating the effects of pesticides focus on the active ingredient, commercial formulations are complex mixtures of several components that may alter their toxicological profile. In this study, we analyzed four pesticides commonly used in corn cultivation, and their typical field mixtures, including the herbicides atrazine and pendimethalin, the insecticides chlorpyrifos and cypermethrin, and a fertilizer, to evaluate their genotoxic effects, oxidative status, and potential to induce cellular transformation. CHO-K1 cells were treated with subtoxic doses of these formulations. MTS, comet, micronucleus, H2AX expression, SOD and GPx activity, and wound healing assays were performed. The results showed these formulations induced genotoxicity, evidenced by the comet assay. Additionally, exposure activated cellular DNA repair mechanisms, evidenced by a 1.89- to 2.63-fold increase in H2AX expression across all treatments and mixtures after 10 h. Notably, pendimethalin was associated with signs of cellular transformation, as evidenced by a 1.4-times greater cell migration observed in the wound healing assay. These findings suggest that even at subtoxic concentrations, these pesticide formulations can cause genetic damage and potentially alter cellular control mechanisms.